A preliminary study on the differential expression of long noncoding RNAs and messenger RNAs in obese and control mice. Issue 2 (28th August 2019) - Li, Ping; Chen, Xiaoyu; Chang, Xuelian; Tang, Tiantian; Qi, Kemin
Abstract: Obesity has become one of the public health problems that threatens children's health, but its specific etiology and pathogenesis are still unclear. Recently, many long noncoding RNAs (lncRNAs) have been shown to be involved in the occurrence of obesity. However, their roles are still poorly understood. Thus, the aim of this study was to discover the profiles of the lncRNAs and messenger RNAs (mRNAs) altered in obesity. Epididymal fat samples were collected from mice fed with control and high‐fat diets (HFD) for 16 weeks to investigate the differentially expressed lncRNAs and mRNAs by lncRNA microarray, after which seven lncRNAs and nine mRNAs were validated using reverse‐transcription polymerase chain reaction (RT‐PCR). Bioinformatics analysis and predictions were used to determine the potential biofunctions of these differentially expressed lncRNAs. Then a coexpression network was constructed to determine the transcriptional regulatory relationship of the differentially expressed lncRNAs and mRNAs between the control and HFD groups. The body weight of the HFD group was much higher than that of the control group, as a result of the increased energy intake. In total, 8421 differentially expressed lncRNAs and 6840 mRNAs were profiled using the lncRNAs microarray. Bioinformatics predictions and the coexpression network all indicated that the occurrence of obesity was attributed to those differentially expressed lncRNAs and mRNAs associated with energy metabolism, cell differentiation, and oxidative phosphorylation. The expression levels of Cyp2e1, Atp5b, Hibch, Cnbp, Frmd6, Ptchd3, ENSMUST00000155948, AK140152, ENSMUST00000135194, and ENSMUST00000180861 were significantly different between the control and HFD groups. All these Results suggested that obesity was partially attributed to those lncRNAs associated with energy metabolism, cell differentiation, and oxidative phosphorylation. Abstract : Hierarchical cluster of heat map showed the different expressions of long noncoding RNAs (lncRNAs) (a), messenger RNAs (c), and top 20 significant upregulated and downregulated lncRNAs (b) with the comparison between the control and high‐fat diet (HFD) groups. Each column represents samples from the control and HFD groups.